PERSEPSI MASYARAKAT TENTANG AKSESIBILITAS DI KORONG SALISIKAN KENAGARIAN SUNGAI BULUH KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Hasanah, Susilawatul - (Pendidikan Geografi, 2014)
This study aims to describe and analyze public perception of the accessibility of the surroundings Salisikan Kenagarian Reed River subdistrict of Batang Anai Padang Pariaman district , in terms of : 1 ) Distance . 2 ) Supporting Facility . 3 ) Infrastructure Support . This type of research used in this study is a qualitative analysis of research in the area of research sites Korong Salisikan District of Batang Anai . The infornan in this study of 33 people covering Wali Nagari , Mayor Korong , youth leader , and the surrounding community by using the techniques of documentation , observation and interviews . Accuracy of data is tested using the data trigulasi , from the data collected were analyzed by using a model consisting of a snowball sampling data collection , data reduction , data presentation and conclusion. The results showed that : the public perception of accessibility in the surroundings Salisikan Kenagarian Reed River subdistrict of Batang Anai Padang Pariaman district are 1 ) Distance , in general, very rarely affects the public both in activities and in taking the existing infrastructure . 2 ) Means of supporting , that damage to facilities ( roads and bridges ) that exist and the lack of assistance from the government to make people difficult to perform daily activities . 3 ) Infrastructure support , that the limited infrastructure ( health centers and markets ) made government makes people take pains , both in taking existing infrastructure elsewhere and are quite far away, and in doing daily activities . Seen from a distance , the existing infrastructure of this region surroundings make people expect help from the government to repair roads , bridges and building health centers this dikorong .